Developing a Jewish Genealogy Library The Israel Genealogical Society Library as a Case Study - Kasow, Harriet ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 2000)
This paper discusses sources specific to Jewish genealogical research and shows how the collection resources of the Israel Genealogical Society (IGS) library have exemplified this. The paper begins with a description of basic genealogical sources available at public, state, and university libraries. Examples of sources unique to Jewish genealogical research are then listed, including Yizkor books, Rabbinical dynastic literature, Holocaust lists and literature, Jewish reference books, journals of various Jewish Genealogical Societies, and the Jewish Genealogical Discussion list. Historical background on the IGS is provided, and the IGS collection is described, including specialized software and information source files, audiovisual materials, and periodicals. Appendices include: (1) a list of Jewish genealogical research World Wide Web sites, (2) a subject index of the IGS genealogical library, including headings for general works, family names, place names, and periodicals; (3) the cover page of the IGS's journal "Sharsharet Hadorot"; and (4) a selected bibliography of research sources relating to Jewish genealogical research, including 25 books and articles, six periodicals, four discussion groups, and five videos. (MES)
Availability: For full text: http://www.ifla.org/IV/ifla66/papers/078-174e.htm.
ERIC Note: In: IFLA Council and General Conference: Conference Proceedings (66th, Jerusalem, Israel, August 13-18, 2000); see IR 057 981.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Case Studies; Foreign Countries; Genealogy; Information Sources; Judaism; Library Collections; Special Libraries; World Wide Web; Israel; Israel -- Web Sites; Reports, Descriptive; Speeches/Meeting Papers